The Role of Imperial Women in the Monetary Distributions (Liberalitas) in Rome in the Light of Numismatic Sources - Balbuza, Katarzyna (Studia Historiae Oeconomicae, 2019)
Liberalitas was one of the most important forms of social activities of the Roman emperors. In quantitative terms, it is also one of the five most important imperial virtues. It appeared on coins as Liberalitas Augusti, which gave this virtue an additional, divine dimension. The first Empress to depict the idea of imperial generosity on the coins issued on her behalf was Julia Domna. In this respect, her liberalitas coins mark a breakthrough in the exposition of this imperial virtue. The well-known female liberalitas coin issues, or imperial issues with empresses’ portraits, date back to the third century and clearly articulate the liberalitas, both iconographically and literally, through the legend on the reverse of the coin. Other coins, issued on behalf of the emperors (mainly medallions), accentuate in some cases (Julia Mamaea, Salonina) the personal and active participation of women from the imperial house in congiarium-type activities. The issues discussed and analysed, which appeared on behalf of the emperors or the imperial women – with a clear emphasis on the role of women – undoubtedly demonstrate the feminine support for the emperor’s social policy towards the people of Rome, including the various social undertakings of incumbent emperors, to whom they were related. They prove their active involvement and support for the image of the princeps created by the emperors through the propaganda of virtues (such as liberalitas). The dynastic policy of the emperors, in which the empresses played a key role, was also of considerable importance.